Utilizing Smart Objects, Smart Filters, and Layers for Nondestructive Radiology Image Editing - Mahesh Thapa; George Taylor (Association of American Medical Colleges, 2010)
Abstract The latest versions of Photoshop have introduced powerful and useful tools to radiologists. By using the program's Smart Objects, Smart Filters, and Layers, we can now preserve the original quality of our images and perform nondestructive, reversible adjustments to them. In this resource, we introduce a novel method to edit radiology images nondestructively and provide a tutorial to guide the reader through the process. A master file contains our original image with various smart filters and layers. These filters and layers can then be adjusted to fit our needs, such as for web presentations, print publications, and projections. The authors have used the methods described in this resource to manipulate and save images for various publications and presentations.